Mineral Paste Comparison Between Copper and Iron Tails - Hernández, CA; Pizarro, EA; Molina, JA; de Araujo, AC; Valadão, GES (Paste 2009: Proceedings of the Twelfth International Seminar on Paste and Thickened Tailings, 2009)
Low-water content mineral tailings disposal has been the focus of study of many scientists, academicians, and engineers in the mining industry. In countries like Canada and Australia, several mineral paste tails disposal pilot and industrial scale test have been successfully carried out, both surface and underground. Chile is the world’s largest copper producer and the main deposits are located in the country’s driest region, therefore, the Chilean companies with concentration operations have focused on the use of sea water, such as Minera Esperanza project (given its favourable geographic location compared to other operations), or extra water recovery through tails thickening, that makes mineral paste technology attractive. Some companies have already undertaken preliminary studies and pilot tests, but in Chile, it is still a new technology. Brazil, South America’s largest steel producer, has also worked on this idea. Some iron deposits have begun to dispose of their tails as mineral paste. These tailings contain a high iron concentration, as it could be expected in some Chilean copper deposits, located between regions 3 and 4. This work aims at comparing the properties of mineral pastes, such as consistency, fluidity and viscosity, from the samples studied in the UFMG, Brazil (high iron content), to recent studies conducted by UNAP, Chile, using Chilean tailings (high magnetite content).